2007
DOI: 10.1097/bcr.0b013e31802cb84f
|View full text |Cite
|
Sign up to set email alerts
|

The Early Acute Phase Response After Burn Injury in Mice

Abstract: In the hours immediately after burn injury, the body enters into an acute phase reaction characterized, in part, by the augmentation of cytokine and acute phase protein production. This reaction has been poorly characterized in the 24 hours immediately after injury. To better understand the early acute phase response, 8- to 10-week-old BALB/C female mice were subjected to a 15% total body surface area (TBSA). Hepatic levels of tumor necrosis factor-alpha, interleukin-1beta, and interleukin-6 were monitored. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Previous studies in thermally injured mice demonstrate significant systemic increases in TNF-␣ at 6 h postburn and IL-1␤ levels 12 h postburn (11,25). These cytokines are known to prime neutrophils by increasing phosphorylation of p38 (6,40).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies in thermally injured mice demonstrate significant systemic increases in TNF-␣ at 6 h postburn and IL-1␤ levels 12 h postburn (11,25). These cytokines are known to prime neutrophils by increasing phosphorylation of p38 (6,40).…”
Section: Discussionmentioning
confidence: 93%
“…Proinflammatory cytokines IL-1β, IL-6, and TNF-α, either alone or in combination can increase the production of SAA in mammals (Betts et al 1993;Ray et al 1999;Hagihara et al 2004). IL-1β and IL-6 play an important role in initiating the acute phase response to inflammation in mammals (Hazuda et al 1990;Fujihashi et al 1992;Gauldie et al 1992;Plackett et al 2007). It has also been suggested that IL-6 is as a key cytokine for the induction of AA-amyloidosis in mammals and that IL-6 blocking therapy normalizes the serum SAA levels and appears promising for the treatment of AA-amyloidosis in mammals (Hagihara et al 2004;Mihara et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Severe burns generally associated with systemic inflammatory response syndrome (SIRS) with attributed alteration of proinflammatory and anti-inflammatory cytokines in the early postinsult period [8,9]. Cytokines and growth factors can influence the expression of MMPs and TIMPs significantly [10], and therefore, the balance of MMP-TIMP system could be altered during the early postinjury period.…”
Section: Introductionmentioning
confidence: 99%